Effects of screened particle sizes and wood: Polypropylene mixing ratio on the physical and mechanical properties of rubberwood plasticcomposites / Nurrohana Ahmad ...[et al.] - Ahmad, Nurrohana; Kasim, Jamaludin; Wan Mohd Nor, Wan Mohd Nor Safizu; Rosman, Norhafizah (2013)
Rubberwood sawdust is the main waste from furniture industries that has potential to be used as wood plastic composites (WPCs). Production of wood plastic composites might be the solution to decrease the wastes from furniture industries. The objectives of this research are to determine the physical and mechanical properties of wood plastic composite using polypropylene as matrix. The ratio of wood particles used in the study were 10%, 20% and 30%, while size of wood particle varied at 150um, 180um and 250um. The strength properties were tested for bending and tensile test and the physical properties of water absorption rates and thickness swelling were based on ASTM standards. Smaller particles and 10% of wood ratio showed better physical and mechanical properties of wood plastic composite.